HUBUNGAN ANTARA PRESTASI PRAKTIK KERJA INDUSTRI DAN HASIL BELAJAR PRAKTIK KELISTRIKAN OTOMOTIF DENGAN MINAT BERWIRAUSAHA SISWA KELAS XII JURUSAN TEKNIK KENDARAAN RINGAN DI SMK N 2 KOTA BIMA - Edy Rahmat Sofyan; Subagyo Subagyo (Jurnal Taman Vokasi, 2015)
This study aimed to describe: (1) correlation between job training achievement with interest in entrepreneurship among the twelfth grade students of state vocational high school 2 Kota Bima; (2) correlation automotive electrical achievement with interest in entrepreneurship among the twelfth grade students of state vocational high school 2 Kota Bima; dan (3) correlation between job training achievement and automotive electrical achievement with interest in entrepreneurship among the twelfth grade students of state vocational high school 2 Kota Bima. The type of this study was ex-post facto. Data collecting methods were questionnaires and documentation. Data analyzing methods used descriptive analysis, first and second hypothesis testing used partial correlation and third hypothesis testing used double regression that was started by normality test, linearity test, and independence test. This study shows that: (1)  there was a positive and significant correlation between job training achievement with interest in entrepreneurship among the twelfth grade students of state vocational high school 2 Kota Bima; (2) there was a positive and significant correlation between automotive electrical achievement with interest in entrepreneurship among the twelfth grade students of state vocational high school 2 Kota Bima; dan (3) there was a positive and significant correlation between job training achievement and automotive electrical achievement with interest in entrepreneurship among the twelfth grade students of state vocational high school 2 Kota Bima. The score of determinant coefficient (R²) was 0.365, it means that job training achievement and automotive electrical achievement gave positive contribution with interest in entrepreneurship 36.5%, while 63.5% was influenced by another factors that were not discussed in this research.